2014
DOI: 10.1120/jacmp.v15i4.4632
|View full text |Cite
|
Sign up to set email alerts
|

ACR testing of a dedicated head SPECT unit

Abstract: Physics testing necessary for program accreditation is rigorously defined by the ACR. This testing is easily applied to most conventional SPECT systems based on gamma camera technology. The inSPira HD is a dedicated head SPECT system based on a rotating dual clamshell design that acquires data in a dual-spiral geometry. The unique geometry and configuration force alterations of the standard ACR physics testing protocol. Various tests, such as intrinsic planar uniformity and/or resolution, do not apply. The Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…The aim of the present study was to reproduce previous findings [ 6 ] and to evaluate additional phantom measurements relevant for DAT imaging. Therefore, in addition to typical NEMA testing setup for gamma cameras (NU 1-2012) [ 7 ], several tests were adapted from NU 2-2012 [ 8 ], originally designed to evaluate performance of PET systems, to augment conventional SPECT testing.…”
Section: Methodsmentioning
confidence: 91%
See 2 more Smart Citations
“…The aim of the present study was to reproduce previous findings [ 6 ] and to evaluate additional phantom measurements relevant for DAT imaging. Therefore, in addition to typical NEMA testing setup for gamma cameras (NU 1-2012) [ 7 ], several tests were adapted from NU 2-2012 [ 8 ], originally designed to evaluate performance of PET systems, to augment conventional SPECT testing.…”
Section: Methodsmentioning
confidence: 91%
“…The aim of the present study was to examine the performance of the system in more detail with respect to clinical DAT imaging. By scanning a small Jaszczak phantom, Sensakovic et al [ 6 ] showed that the InSPira surpassed American College of Radiology (ACR) requirements. The present study aimed to reproduce previous findings by Sensakovic et al [ 6 ] on visible spheres, sphere contrast, visible rod groups, and uniformity using a small Jaszczak phantom.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different image quality parameters such as uniformity, root mean square (rms) value, and contrast[ 12 ] were computed for each data set of SPECT/CT images, obtained by external filter and that without any external filter. Parameters were then compared and studied for change in different image sets.…”
Section: Methodsmentioning
confidence: 99%
“…The InSPira HD system (InSPira; Neurologica, Danvers, MA, USA) is a novel brain-dedicated single-photon emission computed tomography (SPECT) system which differs from conventional SPECT scanners with respect to hardware configuration and scanning geometry [ 1 ]. Performance of the InSPira system was investigated extensively using phantom data by our group [ 2 ].…”
Section: Rationalementioning
confidence: 99%